INNOVATION FOR MANUFACTURING FERTILIZER FROM COFFEE LEATHER WASTE FOR THE COMMUNITY AND FARMER GROUP IN BONDOWOSO - Rini Devijanti Ridwan; Indeswati Diyatri; Sidarningsih; Yuliati (Universitas Airlangga, 2022)
The coffee husk waste has not been utilized optimally by farmers. Coffee skin waste, which has been considered as a leftover material from the production of ground coffee, turns out to have many benefits and uses in life. Based on the results of research by experts, coffee husk waste is useful in agriculture, animal husbandry and fisheries, namely as compost, protein nutrition and additional fiber in animal feed. This solid waste of coffee rind has high levels of organic matter and nutrients that can improve soil structure. One of the efforts that can be done to handle the increasing amount of coffee husk waste is by processing coffee skin waste into compost. The by-products in the form of coffee skins range from 50-60 percent of the harvest. If the yield is 1000 kg of fresh coffee, then about 400-500 kg of coffee beans will be produced and the rest is a by-product in the form of coffee husks. The advantage of this coffee skin compost is that its nitrogen content is quite high, around 6% so that it can substitute for fertilizers containing nitrogen. The problem is that the C/N ratio is high enough that it takes a long time to decompose or the solution is to add nitrogen sources and a decomposer to speed up decomposition. This community service activity was carried out in collaboration with the community in the Bondowoso district, namely the KAPAS Community in Sumbergading Village, Sumberwringin District and the TSS community in Sukosari Lor Village, Sukosari District. In the Bondowoso area, there are many youth communities with various activities aimed at advancing people's lives and improving the socio-economic status of the area. Coffee husk waste is very common in the area, so far, coffee skin waste has not been used optimally, so its benefits cannot be obtained. The solutions offered in this community service activity include: Provide an understanding of the importance of utilizing existing coffee husk waste for communities and communities in the Bondowoso area, Provide training on making fertilizer from coffee husk waste as an innovation in making fertilizer to increase agricultural yields in the Bondowoso area, Exploring and empowering the natural potential that exists in the community environment so that it can be put to good use, Initiate the business of making fertilizer from coffee husk waste as an innovation in making fertilizer for cost efficiency in agriculture Keywords : waste, coffee husk, innovation, fertilizer, health DAFTAR PUSTAKA Dzung NA., Dzung TT.,Khanh VTP.,2013. Evaluation of Coffe Husk Compost for Improving Soil Fertility and Sustainable Coffee Production in Rural Central Highland of Vietnam. Resources and Environment, 3(4), 77-82 Abdoellah, S dan A.Wardani. 1993. Impact of Cocoa Development on Marginal Land to Farmers Income: A Case in Gunung Kidul Regency, Indonesia. Pelita Perkebunan, 9(3), 97 – 104 Bressani, R.1979. The by-products of coffee berries.dalam coffee pulp: composition, technology, and utilization. Editor J. E. Braham and R. Bressani. Ottawa: Institute of Nutrition of Central America and Panama. Berlian, Z., Syarifah, dan Sari DS., 2015. Pengaruh Pemberian Limbah Kulit Kopi (Coffea robusta L.) terhadap Pertumbuhan Cabai Keriting (Capsicum annum L.). Jurnal Biota, 1(1), 22-32. Sahputra, A., Barus A., dan Sipayung R., 2013. Pertumbuhan dan produksi bawang merah (Allium ascalonicum L.) terhadap pemberian kompos kulit kopi dan pupuk organik cair. Jurnal Online Agroekoteknologi, 2(1), 26-35. Maruli, A. 2010. Limbah kopi antar mahasiswa ke jerman. http://www.antaranews.com/berita/2 27334/limbah-kopi-antarmahasiswake jerman/2017.07.18. Afrizon, 2015. Potensi Kopi Sebagai bahan Baku Pupuk Kompos Di Propinsi Bengkulu. AGRITEPA, 2(1). 1, 21-32 Novita E., Fathurrohman A., Pradana HA.,2018. Pemanfaatan Kompos Blok Limbah Kulit Kopi sebagai Media Tanam. Jurnal Agrotek, 2(2), 61- 72 Muryanto, 2004 Muryanto. (2004). Potensi Limbah Kulit Kopi Sebagai Pakan Ternak. Jurnal Lokakarya, 1, 112-114. Triawan DA., Banon C., Adfa M., 2020. Biokonversi Kulit Kopi Menjadi Pupuk Kompos Pada Kelompok Tani Pangestu Rakyat Kabupaten Rejang Lebong. Jurnal Pengabdian Al-Ikhlas, 5(2), 159-165